Technology Development of Kupang Processing with Dryer Machine Base on Expert System - Dedin F Rosida; Dedid Cahya Happyanto (IPTEK Journal of Proceedings Series, 2014)
Kupang as one of traditional food in East Java is an asset that has a positive impact on the nutritional status and health of those who consume them. Efforts to accelerate the realization of the preservation movement kupang through "I love Indonesian food" can be done in addition to providing information support for scientific study and rational accurate about the benefits and safety of those who consume should be developed kupang sale value processed products. Of nutritional aspects in addition to a high protein, apparently in mussels also contained the unsaturated fatty acid chain length is relatively high for good health. Kupang-based optimization of food processing is desirable. Balonggabus village of Candi Sidoarjo District is a regional producer of mussels and the potential to continue to develop products using a variety of mussels to the processed form of dryer machine (cabinet dryer) based on expert system so that the resulting product would be great texture, aroma and taste. Various processed mussels that can be developed such as: instant kupang paste, Kupang flour, Kupang crackers, noodles mussels, mussels etc so that products become more durable. This will make the area Balonggabus be more independent in producing and increasing revenue